Harmonious Industrial Relations in Increasing Company Productivity in The Era of Globalization - Marbun, Rika Jamin; Agusmidah; Uwiyono, Aloysius; Affila (Ultimate Journal of Legal Studies, 2024)
The company plays a crucial role in driving Indonesia's economy, necessitating its sustainability for competitiveness in the global era. Company productivity, which hinges on worker welfare, is vital for maintaining a company's existence. Workers valued by their company will be more productive, as company productivity starts with work productivity. Achieving this requires tranquility and industrial peace in labor relations. This research explores the connection between worker and company productivity, and how company productivity can be achieved through harmonized industrial relations and strengthened communication in the globalization era. Using a normative juridical method, examining laws and regulations, the study highlights the importance of maintaining harmonious industrial relations for work and business peace. Equalizing perceptions between employers and workers and maintaining effective communication are crucial for this goal. Enhancing company productivity begins with business tranquility and aligns with improving workers' welfare. Such conditions are essential for sustaining the company as an economic driver in Indonesia. High productivity enables companies to exist and compete in the global era.